Fabricating Organized Elastin in Vascular Grafts - Wang, Ziyu; Liu, Linyang; Mithieux, Suzanne M.; Weiss, Anthony S. (Trends in biotechnology (Regular ed.), 2021)
Surgically bypassing or replacing a severely damaged artery using a biodegradable synthetic vascular graft is a promising treatment that allows for the remodeling and regeneration of the graft to form a neoartery. Elastin-based structures, such as elastic fibers, elastic lamellae, and laminae, are key functional components in the arterial extracellular matrix. In this review, we identify the lack of elastin in vascular grafts as a key factor that prevents their long-term success. We further summarize advances in vascular tissue engineering that are focused on either de novo production of organized elastin or incorporation of elastin-based biomaterials within vascular grafts to mitigate failure and enhance enduring in vivo performance. A lack of elastin contributes to vascular graft failure modes, including aneurysm, thrombosis, and intimal hyperplasia.Organized elastin synthesis during vascular graft remodeling is limited.De novo elastin production can be stimulated in vitro by using elastogenic smooth muscle cells in combination with the use of biochemical molecules and biomechanical stimuli.Continuous elastic fiber regeneration can be promoted by providing biaxial biomechanical stimulation.Elastin-based recombinamer-functionalized vascular grafts prevent thrombosis and promote endothelium formation.Tropoelastin can be stabilized by heating and incorporated into vascular grafts as a structural component to provide elasticity.Elastic lamina can be extracted without other extracellular matrix components, and decellularized internal elastic lamina is a functional blood-contacting surface.